Pengembangan Media Powerpoint Interaktif Untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa Kelas VIII SMP Negeri 2 Terara Tahun Ajaran 2024/2025 - Dinisa Putri, Baiq Elda; Azmi, Syahrul; Primajati, Gilang; Baidowi, Baidowi (FKIP Universitas Mataram, 2025)
This research aims to develop interactive powerpoint media based on the classpoint application that was feasible, practical and effective to improve the mathematical communication skills of class VIII students at SMP Negeri 2 Terara on the Pythagorean theorem material. This development research uses a 4D model, namely Define, Design, Development and Disseminate. Data in this research are obtained from the results of instrument validation by experts to measure the suitability of the media, the results of teacher and student response questionnaires to measure the practicality of the media, and the results of students' mathematical communication ability tests to measure the effectiveness of the media. The sample in the research are 28 students in class VIII D. Interactive powerpoint media is tested to be very feasible with a validation score of 0,86 and obtained a practicality percentage of 90% and 96.5% with a very practical category. The average student pretest and posttest scores are 70.75 and 88.32, the t-test results showing that there is a difference in the average between the students' pretest and posttest results. The level of media effectiveness is categorized as very effective with an effect size score of 2.0001. Based on the research results, it can be concluded that the development of interactive powerpoint media is feasible, practical and effective for improving the mathematical communication skills of class VIII students at SMPN 2 Terara for the 2024/2025 academic year.